If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 92 = -4(1 + -4r) 92 = (1 * -4 + -4r * -4) 92 = (-4 + 16r) Solving 92 = -4 + 16r Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-16r' to each side of the equation. 92 + -16r = -4 + 16r + -16r Combine like terms: 16r + -16r = 0 92 + -16r = -4 + 0 92 + -16r = -4 Add '-92' to each side of the equation. 92 + -92 + -16r = -4 + -92 Combine like terms: 92 + -92 = 0 0 + -16r = -4 + -92 -16r = -4 + -92 Combine like terms: -4 + -92 = -96 -16r = -96 Divide each side by '-16'. r = 6 Simplifying r = 6
| ln(X+5)-2=ln(7-x)+3 | | x^3-7x^2-53x+315=0 | | 3x+2-= | | -2y-18=5y+3 | | 7r-3r+5=1+10-4r | | (x^2-9)(x+2)=0 | | 7x-12+2x+9+2x+9=180 | | 2*f=-46 | | 6x+3+6-2= | | 3/4=45 | | y-0.5y=4.5 | | 9a+8-7= | | 0.2(3+p)=4.6 | | X=1/2(3X-2)+2 | | -16+3n=8n-3(n-4) | | X=1/2(3X-2+2) | | 20y^2=21y-4 | | 3(x+8)-8=3x-19 | | cos^2(4x)+cos(4x)=0 | | X=1/2(3X-2) | | m^2-20=8m | | 7x^2+6x=5 | | X=2(3X-2) | | -6(x-10)=-12 | | 5x^6y^3= | | 25X=2(3X-2) | | -3x-5=4x-6 | | 685=85-2x | | a=bh/2 | | (8+2x)5=-28x+2 | | -4(x+2)=-8 | | 1.5(2e-30)+2e=135 |